Pengungkapan Fraudulent Financial Statement Pada Bank Umum Syariah - Puspa Kartika Cahyani; Arna Asna Annisa (IQTISHADUNA, 2021)
Abstract This research purpose to examine the effect on fraud diamond toward the fraudulent financial statement. This research uses sampel in islamic comersial banks that listed in financial service authority from 2015-2019. The number of population in this research are 14 islamic comersial bank with five years observation. Based on purpossive method, total of research samples are 55 financial statement. The hypothesis in this research is tested by multiplied regression analyze. The result of this research indicates that the financial stability and rationalization effect toward the fraudulent financial statement. However, financial target, external pressure, ineffective monitoring, and capability don’t effect toward the fraudulent financial statement.